Pengaruh Rasio Rentabilitas, Profitabilitas, dan Rasio Aktivitas Terhadap Kinerja Keuangan (Studi Kasus Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021) - Ana Adinda Sofiyah; Afifudin Afifudin; Siti Aminah Anwar (Universitas Islam Malang, 2023)
The company's financial performance is one of the factors seen by potential investors, where healthy and efficient financial performance will result in the company obtaining high profits (profits). then the tool commonly used is the financial ratio. The purpose of this study was to determine the effect of profitability, profitability, and activity ratios on financial performance in manufacturing companies listed on the IDX from 2019-2021. The types and sources of data used in this study are secondary data, using a quantitative approach which is an empirical research, sampling in this study was carried out using purposive sampling technique. Profitability, Profitability, and Activity Ratios have a positive and significant impact on financial performance, the F value is 133.738 with a significant value of 0.000, which is smaller than 0.05.Keyword: Profitability ratios, profitability ratios, activity ratios, financial performance